2018
DOI: 10.1253/circj.cj-17-1220
|View full text |Cite
|
Sign up to set email alerts
|

Outcome From a Randomized Controlled Clinical Trial ― Improvement of Peripheral Arterial Disease by Granulocyte Colony-Stimulating Factor-Mobilized Autologous Peripheral-Blood-Mononuclear Cell Transplantation (IMPACT) ―

Abstract: poietic stem cells in human peripheral blood (PB) and that transplantation of CD34 + cells promotes angiogenesis in animal models of lower-limb ischemia, 1 which drew attention to hematopoietic cells as a new therapeutic modality in ischemic diseases. Background: The clinical usefulness of peripheral blood (PB) mononuclear cell (MNC) transplantation in patients with peripheral arterial disease (PAD), especially in those with mild-to-moderate severity, has not been fully clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…It has been reported that one method among the cell therapies that promote peripheral circulation is therapeutic angiogenesis using bone marrow-derived mononuclear cells (BM-MNC). [8][9][10] The first clinical pilot study, Therapeutic Angiogenesis by Cell Transplantation (TACT) study, investigated this in CLI patients in 2002, 11 and subsequently, several studies have reported the safety and efficacy of BM-MNC implantation for CLI patients. 12,13 Randomized studies have reported that this cell therapy could lead to significant improvements in limb ischemia, thus extending amputation-free intervals and survival rates.…”
Section: Study Populationmentioning
confidence: 99%
“…It has been reported that one method among the cell therapies that promote peripheral circulation is therapeutic angiogenesis using bone marrow-derived mononuclear cells (BM-MNC). [8][9][10] The first clinical pilot study, Therapeutic Angiogenesis by Cell Transplantation (TACT) study, investigated this in CLI patients in 2002, 11 and subsequently, several studies have reported the safety and efficacy of BM-MNC implantation for CLI patients. 12,13 Randomized studies have reported that this cell therapy could lead to significant improvements in limb ischemia, thus extending amputation-free intervals and survival rates.…”
Section: Study Populationmentioning
confidence: 99%
“…In these so-called no-option CLI (NO-CLI) patients, the prognosis appears to be even worse, with a major amputation rate of 40% at 6 months from onset [2]. Novel approaches of stem cell-based therapeutic angiogenesis, including bone marrow- (BM) or peripheral blood (PB)-derived mononuclear cell (MNC) transplantation with or without purification of specific cell types, are increasingly being used in clinical trials that attempt to treat NO-CLI [513]. These phase I/II trials have confirmed the safety and feasibility of MNC transplantation and revealed its potential therapeutic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Ozturk et al (57) reported better improvement of Fontaine score, ABI, TcPO2, and pain score in diabetic CLI patients treated with G-CSF mobilized PBMNC compared to control subjects treated with stand-ard of care. Additionally, a more recent larger-scale randomized clinical trial by Horie et al (87) using G-CSF mobilized PBMNC transplantation showed that PBMNC therapy was able to significantly improve the progressionfree survival of mild-to-moderate PAD.…”
Section: Clinical Trials Of Stem Cell Therapy For Pad In Diabetes Patmentioning
confidence: 99%